Comparison of antihypertensive activity of beta-blocking drugs during chronic treatment. Issue 6026 (3rd July 1976) - Davidson, C; Thadani, U; Singleton, W; Taylor, S H
Abstract : The hypotensive activity of five beta-adrenoceptor antagonists with different ancillary pharmacological properties was compared in a randomised double-blind factorial trial in 25 untreated patients with stable, uncomplicated essential hypertension. In doses that produced similar reductions in exercise tachycardia all drugs had similar blood-pressure lowering activity, greater on systolic than diastolic pressure and greatest during exercise. With the exception of vasodilator activity the possession of any particular combinaton of ancillary pharmacological properties did not significantly influence the specific antihypertensive activity of these compounds.